L'économie solidaire en Bolivie. Entre marché et démocratie - Hillenkamp, Isabelle (KARTHALA Editions, 2013)
Depuis les années 1980, de plus en plus de pays ont opté pour une économie de marché et un régime politique de type démocratique et ce, indépendamment de leur « niveau de développement ». Pourtant, marché et démocratie ne sont pas directement compatibles. Si tous deux reposent sur les principes de liberté et d’égalité, le premier mise sur le pouvoir émancipateur du marché libre, alors que la seconde suppose une certaine égalité des conditions de vie. Une lecture croisée de cas européens et latino-américains illustre cette problématique commune, en même temps que la diversité des systèmes de médiations solidaires entre marché et démocratie. Les solidarités, qu’elles soient enracinées dans des structures familiales ou communautaires, instituées dans des systèmes de protection sociale ou organisées dans des groupes de producteurs ou de consommateurs de l’économie solidaire, créent en effet des interdépendances qui amortissent les tensions entre marché et démocratie. En développant cette analyse socioéconomique, Isabelle Hillenkamp propose une approche novatrice des questions de développement. Par des données récoltées auprès d’organisations d’économie solidaire et de nombreux autres acteurs en Bolivie, elle apporte des réponses ancrées dans la complexité d’un terrain de recherche. Isabelle Hillenkamp est titulaire d’un doctorat en études du développement de l’Institut de hautes études internationales et du développement, à Genève. A partir d’enquêtes en Amérique latine, ses travaux portent sur l’économie populaire et solidaire, qu’elle aborde dans une perspective socioéconomique, attentive aux liens entre pratiques économiques et rapports sociaux. Elle est chargée de recherche à l’Institut de recherche pour le développement, en France. Table des matières Introduction, L’économie solidaire en Bolivie, Entre marché et démocratie, Du pluralisme économique à la démocratisation I. Solidarité, marché et démocratie : une problématique européenne et latino-américaine II. Les organisations boliviennes d’économie solidaire : réciprocité et redistribution III. Les organisations boliviennes d’économie solidaire face aux marchés IV. Réciprocité, marché et démocratie : des tensions fondamentales V. La démocratisation de l’économie Ils en ont parlé Présentation du livre dans L'AGEFI, quotidien de l'Agence économique et financière à Genève Critique du livre sur le site Alterinfos, América Latina ENG translation: Since the 1980s, more and more countries have opted for a market economy and a democratic-type political regime, irrespective of their "level of development". Yet market and democracy are not directly compatible. If both are based on the principles of liberty and equality, the first is the emancipatory power of the free market, while the latter assumes a certain equality of living conditions. A cross-reading of European and Latin American cases illustrates this common problem, together with the diversity of solidarity-based mediation systems between market and democracy. Solidarity, whether rooted in family or community structures, instituted in social protection systems or organized in groups of producers or consumers of the solidarity economy, creates interdependencies that dampen tensions between the market and democracy. In developing this socioeconomic analysis, Isabelle Hillenkamp proposes an innovative approach to development issues. Through data collected from organizations of solidarity economy and many other actors in Bolivia, it brings answers anchored in the complexity of a field of research. Isabelle Hillenkamp holds a Ph.D. in Development Studies from the Graduate Institute of International and Development Studies in Geneva. Based on surveys in Latin America, her work focuses on the popular and solidarity economy, which she addresses in a socio-economic perspective, attentive to the links between economic practices and social relations. She is a researcher at the Research Institute for Development in France. Table of Contents Introduction, Solidarity Economy in Bolivia, Between Market and Democracy, From Economic Pluralism to Democratization I. Solidarity, Market and Democracy: A European and Latin American Issue II. Bolivian organizations of solidarity economy: reciprocity and redistribution III. Bolivian organizations of solidarity-based economy versus markets IV. Reciprocity, market and democracy: fundamental tensions V. The democratization of the economy They talked about it Presentation of the book in the AGEFI, the daily newspaper of the Economic and Financial Agency in Geneva Book review on the website Alterinfos, América Latina
Political Science
Keywords: Bolivia; solidarity economy

Socioéconomie et démocratie, l'actualité de Karl Polanyi - Hillenkamp, Isabelle; Laville, Jean-Louis (Toulouse : Érès éd, 2013)
La crise actuelle révèle des tensions fondamentales entre capitalisme et démocratie. L'orthodoxie occidentale, centrée sur les programmes d'ajustement, s'avère incapable d'affronter ce défi à la frontière de l'économie, du social et du politique. Il est temps de se tourner vers d'autres approches. S'appuyant sur l'oeuvre singulière de Karl Polanyi (1886- 1964) qui a décelé la dérive totalitaire de la société de marché, cet ouvrage soumet de nouvelles clés pour penser certains des problèmes les plus ardus de notre temps. Les auteurs, internationalement reconnus, venant d'Amérique et d'Europe, du Sud et du Nord, sont publiés pour la première fois ensemble en langue française. Ils proposent une vision croisée des rapports entre démocratie et économie, à partir de différentes disciplines et de divers terrains d'étude. Cette réflexion collective débouche sur la construction d'un cadre théorique permettant de comprendre la teneur des mutations économiques et politiques contemporaines. Mais elle ne s'arrête pas aux constats critiques. Face à la menace d'une régression autoritaire, elle s'intéresse aux pratiques qui concrétisent des issues solidaires et démocratiques à la crise. ENG: The aim of this book is to mobilize the contribution of Polanyi to think the socio-economy in a perspective of deepening democracy. The book updates the critical analysis of the new globalized capitalism but also identifies socio-economic experiences that can contribute to building more democratic societies in the 21st century.
Political Science; Development Studies
Keywords: démocratie; développement économique - aspect social; economics - sociological aspects; triple movement; économie de marché; économie politique - aspect sociologique; économie sociale; économie sociale et solidaire

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).
History

Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o 1
History
Keywords: CHAPMAN; Anne; POLANYI LEVITT; Kari; ZEMON DAVIS; Nathalie